2019
DOI: 10.1121/1.5096642
|View full text |Cite
|
Sign up to set email alerts
|

Geometric shapes effect of in-duct perforated orifices on aeroacoustics damping performances at low Helmholtz and Strouhal number

Abstract: In this work, experimental studies are conducted to measure the aeroacoustics damping performances of 11 in-duct perforated plates in a cold-flow pipe with a variable Mach number. These in-duct plates have the same porosities but different number N and geometric shaped orifices. Here six shapes are considered, i.e., (1) triangle, (2) square, (3) pentagon, (4) hexagon, (5) star, and (6) circle. It is shown that the orifice shape has little influence on power absorption Δ and reflection coefficient R at a lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Within the measured frequency range, the frequency response of the experimental equipment is less than ±0.2 dB, and the sensitivity of the built-in microphone is 30 mV/Pa. In conclusion, the experimental measurements and findings in this work are applicable to other porosities and other shaped orifices/liners as reported in (Zhao et al ., 2019b).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Within the measured frequency range, the frequency response of the experimental equipment is less than ±0.2 dB, and the sensitivity of the built-in microphone is 30 mV/Pa. In conclusion, the experimental measurements and findings in this work are applicable to other porosities and other shaped orifices/liners as reported in (Zhao et al ., 2019b).…”
Section: Discussionsupporting
confidence: 77%
“…There is alternative model approach such as Lattice Boltzmann method (Ji and Zhao, 2014a, b), which can also be used for the present work. Experimental studies are conducted to measure the aeroacoustics damping performances of in-duct perforated plates in a cold-flow pipe with a variable Mach number in (Zhao et al ., 2019b). It is shown that the orifice shape has little influence on power absorption and reflection coefficient at a lower Helmholtz number.…”
Section: Discussionmentioning
confidence: 99%
“…According to Zhao, 42 it was found that the geometry of the perforation has a non-negligible effect on the acoustic performance of perforated plates in the flow state. This paper will extend to the effect of perforation angle on the acoustic impedance of perforations under the action of swept flow.…”
Section: Effect Of Perforation Angle On Transmission Lossmentioning
confidence: 99%
“…[5][6][7]12 The governing equations are coupled nonlinear Navier-Stokes equations. The vorticity-involved damping physics of Helmholtz resonators are visualized by these simulations 12,13,15 or flow visualizations or laserinvolved experimental measurements. 16 Such time-domain simulations and experimental measurements may be economically costly, and numerically time-costly.…”
Section: Introductionmentioning
confidence: 99%